PENGARUH FAKTOR RISIKO ERGONOMI TERHADAP KELUHAN NYERI PUNGGUNG BAWAH (LOW BACK PAIN) PADA KARYAWAN BUSHINDO TRAINING CENTER JAKARTA TIMUR - Toto Aminoto; Abdurrahman Berbudi (Jurnal Ilmu dan Teknologi Kesehatan, 2017)
To meet the needs of his life then the man is required to work. In the workplace most of the time spent at work. Workplace environment has a risk to the health of people who work in the environment. In a working position that spent too much sitting can cause back pain, especially the bottom (Low back pain). This study aims to prove that the influence of Ergonomic Risk Factors can cause complaints of low back pain employee Bushindo Training Center East Jakarta. The sampling technique used is saturated sampling. The statistical analysis used is simple linear regression analysis. The results showed that ergonomic risk factors had a significant positive effect on the occurrence of low back pain. Ergonomic risk factors contribute to the possibility of lower back pain process by 63.5% the rest influenced by factors other than the variables performed in this study